Category specificity in mind and brain? - Humphreys, G; Forde, E (2001)
We summarise and respond to the main points made by the commentators on our target article, which concern: (1) whether structural similarity can play a causal role in normal object identification and in neuropsychological deficits for living things, (2) the nature of our structural knowledge of the world, (3) the relations between sensory and functional knowledge of objects, and the nature of our functional knowledge about living things, (4) whether we need to posit a "core" semantic system, (5) arguments that can be marshalled from evidence on functional imaging, (6) the causal mechanisms by which category differences can emerge in object representations, and (7) the nature of our knowledge about categories other than living and nonliving things. We also highlight points raised in our article that seem to be accepted.